Dynamics of ultrafast twin beam generation in gas-filled hollow-core photonic crystal fibres - Lippl, Markus; Chekhova, Maria V.; Joly, Nicolas Y. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
It has been shown that noble-gas filled hollow-core photonic crystal fibres (HC-PCFs) are suitable for Raman-free generation of entangled sidebands, both in the low-gain regime for the generation of biphoton states and for bright states in the high-gain regime [1] , [2]. The frequency correlations of the bipartite system and its entanglement properties are often described in terms of time-frequency Schmidt (TFS) modes, which can be extracted from the joint spectral amplitude (JSA). It is however experimentally easier to measure the joint spectral intensity (JSI = |JSA| 2 ), which can also yield valuable information about the source [1]. The major difference between twin beam or biphoton generation in a crystal and in a fibre is that in fibre the propagation dynamics of pump, signal and idler play a bigger role due to the much longer path-lengths.
CRIS-Team Scopus Importer:2021-10-29